Pengaruh Locus Of Control, Equity Sensitivity dan Pengetahuan Etika terhadap Perilaku Etis Mahasiswa Akuntansi - Fitriani, Fitriani; Sari, Vita Fitria (Universitas Negeri Padang, 2024)
This study intends to acertain the effect locus of control, equity sensitivity and moral knowledge of accounting students moral behavior in Padang City. The study population was the accounting students of UNP, UNAND, UPI YPTK and UBH consisting of 1800 accounting students. Samples for this study employing the purposive sampling technique. When determining the number of samples using the Slovin formula, 327 accounting students were used as samples. This research falls under the quantitative approach. The data source utilized in this study primary data by distributing questionnaires to accounting students. The data was subjected to linear regression analysis. The findings of this investigation are as follows : locus of control internal, equity sensitivity and ethical knowledge own a positive effects on the accounting students moral behavior in Padang City.